Optimalisasi Penerapan Seni Tari Turonggoyaakso Di SDN 2 Ngentrong Sebagai Upaya Pelestarian Budaya - Tsania Nuril Faiz; Dita Hendriani (Universitas 45 Surabaya, 2024)
The prospect of local wisdom is very dependent on how people preserve the existing local wisdom and how people change their mindset back to a comprehensive mindset. So that natural resources and the natural environment owned by the community can be utilized and preserved without disturbing its balance. This study aims to determine the optimization of the application of Turonggoyakso dance at SDN 2 Ngentrong as an effort to preserve culture from an early age. The research method used is descriptive qualitative, involving in-depth interviews, participatory observation, and document studies to collect data. Data were analyzed through data reduction, data presentation and verification. The implementation activities carried out by SDN 2 Ngentrong have many benefits, such as a form of cultural preservation, as school branding in attracting the attention of citizens, and there are character education values obtained from these activities.